Analisis Pengaruh Covid-19 Terhadap Manajemen Operasional Pada PT Indofood Sukses Makmur Tbk: Analisis Pengaruh Covid-19 Terhadap Manajemen Operasional Pada PT Indofood Sukses Makmur Tbk - Benny; Adeline Oktalia; Emilya; Lia Willyanto; Lusiana; Monica Ella (Cv. Utility Project Solution, 2023)
In this research will be found how the implementation of operational management carried out by PT. Indofood was able to survive during the Covid-19 pandemic in order to increase the efficiency and effectiveness of its business processes, reduce waste, improve product quality and increase customer satisfaction. The only highly effective and effective way of improving operational performance is to organize and distribute goods or services according to reliable and efficient customer groups. PT Indofood CBP Sukses Makmur Tbk. is a manufacturer of various types of food and beverages located in Jakarta, Indonesia. The method used in this research in collecting data is descriptive method by collecting internet searching data. This helps researchers in improving the data found. In this study the data analysis method used is a qualitative method. By using this method researchers can analyze existing events, then will be followed later with a collection of existing theories in the analysis.